Reorganization of Breeding Institutions to Develop Breeding Stock of Indonesian Holstein - C Talib; A Anggraeni; K Diwyanto (Indonesian Center for Animal Research and Development, 2001)
Development of dairy cattle production through breeding system improvement is not well arranged for guaranteeing a successful to increase capability of Indonesian milk industries. Some constraints that inhibit the programs are only a short-term program available to improve cattle production ie., improvement of rearing and feeding management; a small number of finance available; no appropriate joint-action between breeding institutions; and the operational of recording program and progeny test are very limited. Other factors that also directly or indirectly influence the development of dairy cattle production are only a small number of animal unite is kept by farmer, limited land area per family, no access for banking supported, and relatively small upland area available in comparison to milk requirement in Indonesia. Improvement of breeding program by way of artificial insemination (AI) is good conducted but the problem is the bulls for producing AI’s semen are not tested under Indonesian condition. Therefore, proven bulls that tested in Indonesia has to be priority together with identification for highly producing cows. All activities can be well organized if the recording program recorded by farmer or some one else and all breeding institutions can rearrange their programs to produce a better mechanism for supporting Indonesian milk industries. Key words: Institution, breeding, Indonesian Holstein